Risk factors for intracerebral hemorrhage in small-vessel disease and non-small-vessel disease etiologies—an observational proof-of-concept study - Arndt, Philipp; Chahem, Christian; Luchtmann, Michael; Kuschel, Jan-Niklas; Behme, Daniel; Pfister, Malte; Neumann, Jens; Görtler, Michael; Dörner, Marc; Pawlitzki, Marc; Jansen, Robin; Meuth, Sven G.; et al. (Frontiers in Neurology, 2024)
Background Sporadic cerebral small-vessel disease (CSVD), i.e., hypertensive arteriopathy (HA) and cerebral amyloid angiopathy (CAA), is the main cause of spontaneous intracerebral hemorrhage (ICH). Nevertheless, a substantial portion of ICH cases arises from non-CSVD etiologies, such as trauma, vascular malformations, and brain tumors. While studies compared HA- and CAA-related ICH, non-CSVD etiologies were excluded from these comparisons and are consequently underexamined with regard to additional factors contributing to increased bleeding risk beyond their main pathology. Methods As a proof of concept, we conducted a retrospective observational study in 922 patients to compare HA, CAA, and non-CSVD-related ICH with regard to factors that are known to contribute to spontaneous ICH onset. Medical records (available for n = 861) were screened for demographics, antithrombotic medication, and vascular risk profile, and CSVD pathology was rated on magnetic resonance imaging (MRI) in a subgroup of 185 patients. The severity of CSVD was assessed with a sum score ranging from 0 to 6, where a score of ≥2 was defined as advanced pathology. Results In 922 patients with ICH (median age of 71 years), HA and CAA caused the majority of cases (n = 670, 73%); non-CSVD etiologies made up the remaining quarter (n = 252, 27%). Individuals with HA- and CAA-related ICH exhibited a higher prevalence of predisposing factors than those with non-CSVD etiologies. This includes advanced age (median age: 71 vs. 75 vs. 63 years, p < 0.001), antithrombotic medication usage (33 vs. 37 vs. 19%, p < 0.001), prevalence of vascular risk factors (70 vs. 67 vs. 50%, p < 0.001), and advanced CSVD pathology on MRI (80 vs. 89 vs. 51%, p > 0.001). However, in particular, half of non-CSVD ICH patients were either aged over 60 years, presented with vascular risk factors, or had advanced CSVD on MRI. Conclusion Risk factors for spontaneous ICH are less common in non-CSVD ICH etiologies than in HA- and CAA-related ICH, but are still frequent. Future studies should incorporate these factors, in addition to the main pathology, to stratify an individual’s risk of bleeding.